Cross machine investigation of magnetic tokamak dust; structural and magnetic analysis. (September 2021) - De Angeli, M.; Tolias, P.; Conti, C.; Ripamonti, D.; Ghezzi, F.; Arnas, C.; Irby, J.; Jerab, M.; LaBombard, B.; Lecci, S.; Maddaluno, G.
Abstract: Magnetic dust collected from multiple fusion devices (FTU, Alcator C-Mod, COMPASS) that feature different plasma-facing components (PFCs) and toroidal magnetic fields has been analyzed by means of the X-ray diffraction technique aiming to investigate the nature and origin of dust magnetism. Analysis led to the conclusion that the main mechanism of ferromagnetic dust formation is the change of iron crystalline phase from austenitic to ferritic during the re-solidification of stainless steel droplets. Analysis also revealed differences in the collected dust structure and an unexpectedly high amount of stainless steel based dust in its native austenitic phase. Theoretical estimates showed that the magnetic moment force can also mobilize strongly paramagnetic adhered dust prior to the establishment of proper tokamak discharges. The post-mortem analysis of dust collected during pure magnetic discharges in FTU confirmed these estimates. Highlights: Magnetic dust from various tokamaks was analyzed by means of X-ray diffraction. Magnetic dust was collected from FTU during pure magnetic discharges. The ferromagnetism of SS dust stems from the austenite to ferrite phase change. Strongly paramagnetic SS dust can also be mobilized by the magnetic moment force. Magnetized dust could be an issue during start-up phases in future fusion devices.